He kura huna - Māori expressions of educational success - Martin, Jennifer (Te Kaharoa, 2012)
Western values have long dominated discourse on what constitutes success and achievement in education. New Zealand’s own education system has been described as one which “... gives first priority to academic and western values of success” (Lee, 2008, p. 81). Emphasis is placed upon the individual, academic excellence, literacy and numeracy, economic outcomes, and competence in what western society deems valid knowledge, and as such, current assessment measures are reflective of this. While such measures are accepted as ‘best practice’ for mainstream institutions, it is argued that where indigenous education is concerned, “...success also lies in more holistic ways of knowing and participating within a rich cultural context” (Bell, 2004, p.30). Situated in a Māori world view, this paper considers success through a Māori lens. It is argued that Māori notions of success are not only premised upon academic results, rather cultural factors are considered equally as important to knowledge and understanding of te ao Māori (Māori world view), tikanga Māori (Māori customary practices), whakapapa (genealogy), hītori (histories and tradition) and te reo Māori (the Māori language). This paper seeks to highlight Māori expressions of educational success for Kura Kaupapa Māori (KKM) through the implementation of a holistic approach to education, underpinned by the guiding philosophy, Te Aho Matua. This paper will draw on my doctoral research. Graduates experiences are an integral part of this paper and research, as they give voice and validity to KKM educational success.